Need Analysis of Development Electronic Module Teaching Materials in Rhythmic Gymnastics Course - Oktariyana, Oktariyana; Oktariyani, Oktariyani (Journal of Physical Education Health and Sport, 2020)
This study aims to analyze the learning process in rhythmic gymnastics courses for the Physical and Recreational Education Study Program of the Nahdlatul Ulama University Lampung as a basis for developing electronic module teaching materials for rhythmic gymnastics courses. This research method refers to the stages of the Borg and Gall development model. The data collection technique was carried out by distributing questionnaires to students and interviewing lecturers of rhythmic gymnastics courses. Data analyzed descriptively. The results showed that on average 90% of students have a high interest in learning rhythmic gymnastics courses, but students have not been well facilitated in their learning. So that 100% of students say that it needs to develop electronic module teaching materials in rhythmic gymnastics courses. Also, the learning of rhythmic gymnastics courses takes place well, but learning has not used an innovative and interesting learning model that can clarify the material presented and based on developing technology to facilitate student’s understanding of the material independently. Thus the need to improve teaching materials in the form of electrical modules in rhythmic gymnastics courses